Glomerular damage as a predictor of renal allograft loss - Moscoso-Solorzano,G. (2010)
Interstitial fibrosis and tubular atrophy (IF/TA) are the most common cause of renal graft failure. Chronic transplant glomerulopathy (CTG) is present in approximately 1.5-3.0% of all renal grafts. We retrospectively studied the contribution of CTG and recurrent post-transplant glomerulopathies (RGN) to graft loss. We analyzed 123 patients with chronic renal allograft dysfunction and divided them into three groups: CTG (N = 37), RGN (N = 21), and IF/TA (N = 65). Demographic data were analyzed and the variables related to graft function identified by statistical methods. CTG had a significantly lower allograft survival than IF/TA. In a multivariate analysis, protective factors for allograft outcomes were: use of angiotensin-converting enzyme inhibitor (ACEI; hazard ratio (HR) = 0.12, P = 0.001), mycophenolate mofetil (MMF; HR = 0.17, P = 0.026), hepatitis C virus (HR = 7.29, P = 0.003), delayed graft function (HR = 5.32, P = 0.016), serum creatinine ≥1.5 mg/dL at the 1st year post-transplant (HR = 0.20, P = 0.011), and proteinuria ≥0.5 g/24 h at the 1st year post-transplant (HR = 0.14, P = 0.004). The presence of glomerular damage is a risk factor for allograft loss (HR = 4.55, P = 0.015). The presence of some degree of chronic glomerular damage in addition to the diagnosis of IF/TA was the most important risk factor associated with allograft loss since it could indicate chronic active antibody-mediated rejection. ACEI and MMF were associated with better outcomes, indicating that they might improve graft survival.